Perancangan Blueprint Sistem Informasi Mekanisme Kinerja Bidang Penunjang Dosen Berdasarkan Tel-U POINT Di Fakultas Rekayasa Industri Universitas Telkom Menggunakan Waterfall Model - Pramesti Intan Meuthia; Litasari Widyastuti Suwarsono; Atya Nur Aisha (Universitas Islam Sumatera Utara, 2019)
Higher education is one of the places to develop competencies, which will prepare students (human resources) to become people who have academic and professional abilities. In universities, lecturers carry out the main task known as the Tri Dharma College, namely education and teaching activities, research and development, and community service, while at Telkom University in addition to the Tri Dharma College there are also supporting tasks and special obligations of the professor. In supporting lecturers for supervisory supervision is still subjective and there is injustice in the verification process, as well as collecting data related to supporting lecturers manually. The lack of supervision and the absence of a system in integrating the supporting data resulted in uneven distribution of support (both assignments and points obtained) and the absence of track records for lecturers. So that it requires a proposed business process design, blueprint document design, and the design of a user interface that is in accordance with the penunjang mechanism based on Tel-U Point in the Telkom Industrial Engineering Faculty with interesting and accessible visualization anywhere. With the design of this website-based information support mechanisms, it is expected that the control holders in each process can be clearly illustrated, supporting data can be well integrated, and data filling and storage can be automated in the system.